METHODOLOGY FOR ANALYZING CAPACITY AND LEVEL OF SERVICE USING HCM 2000 - Nedevska Ivana; Zafirovski Zlatko; Ognjenovic Slobodan; Ristov Riste; Gacevski Vasko (Faculty of Civil Engineering - Skopje, 2021)
The augmentation of motorization level leads us to the need for mobility and demands better infrastructure, in urban and suburban areas. The complexity of this problem is especially notable in urban areas where the space delimitations, functional characteristics and different transportation must be considered. The intersection between boulevard Krste Petkov Misirkov and boulevard Goce Delcev, in Skopje, has been analysed with the methodology for capacity and level of service, according to Highway Capacity Manual. Both boulevards are with three lanes before the intersection, and two additional lanes for left and right turns in the intersection area, and this is one of the most frequent intersections in Skopje. Number of vehicles is determined by measuring the traffic, and those inputs are used to analyse three solutions: The current solution (signalized intersection), Roundabout and interchange (levelled roundabout). Calculations are based on custom measurements within a week.
Keywords: intersection, analysis, roundabout, capacity, level of service, Highway Capacity Manual